Pharmacological Inhibition of PPARy Boosts HIV Reactivation and Th17 Effector Functions, while Preventing Progeny Virion Release and de novo Infection - Delphine Planas; Augustine Fert; Yuwei Zhang; Jean-Philippe Goulet; Jonathan Richard; Andrés Finzi; Maria Julia Ruiz; Laurence Raymond Marchand; Debashree Chatterjee; Huicheng Chen; Tomas Raul Wiche Salinas; Annie Gosselin; et al. (Case Western Reserve University, 2020)
The frequency and functions of Th17-polarized CCR6+RORyt+CD4+ T cells are rapidly compromised upon HIV infection and are not restored with long-term viral suppressive antiretroviral therapy (ART). In line with this, Th17 cells represent selective HIV-1 infection targets mainly at mucosal sites, with long-lived Th17 subsets carrying replication-competent HIV-DNA during ART. Therefore, novel Th17-specific therapeutic interventions are needed as a supplement of ART to reach the goal of HIV remission/cure. Th17 cells express high levels of peroxisome proliferator-activated receptor gamma (PPARy), a transcriptional factor that represses the transcription of the HIV provirus and the rorc gene, which encodes for the Th17-specific master regulator RORyt/RORC2. Thus, we hypothesized that the pharmacological inhibition of PPARy will facilitate HIV reservoir reactivation while enhancing Th17 effector functions. Consistent with this prediction, the PPARy antagonist T0070907 significantly increased HIV transcription (cell-associated HIV-RNA) and RORyt-mediated Th17 effector functions (IL-17A). Unexpectedly, the PPARy antagonism limited HIV outgrowth from cells of ART-treated people living with HIV (PLWH), as well as HIV replication in vitro. Mechanistically, PPARy inhibition in CCR6+CD4+ T cells induced the upregulation of transcripts linked to Th17-polarisation (RORyt, STAT3, BCL6 IL-17A/F, IL-21) and HIV transcription (NCOA1-3, CDK9, HTATIP2). Interestingly, several transcripts involved in HIV-restriction were upregulated (Caveolin-1, TRIM22, TRIM5α, BST2, miR-29), whereas HIV permissiveness transcripts were downregulated (CCR5, furin), consistent with the decrease in HIV outgrowth/replication. Finally, PPARy inhibition increased intracellular HIV-p24 expression and prevented BST-2 downregulation on infected T cells, suggesting that progeny virion release is restricted by BST-2-dependent mechanisms. These results provide a strong rationale for considering PPARy antagonism as a novel strategy for HIV-reservoir purging and restoring Th17-mediated mucosal immunity in ART-treated PLWH.